Psikologi Pendidikan Islam dalam Al Qur’an - Kholil, A. Munawar; Rahman, Abdur; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
In general, the development of educational psychology is a branch of psychology that specializes in the scientific study of understanding teaching and learning processes in educational environments. Psychology is not limited to a single branch; rather, it encompasses various fields that are intriguing to explore. One of these is educational psychology. Islamic educational psychology is a field of knowledge dedicated to thoroughly analyzing human behavior as educators, alongside their potential in striving for the perfection of human life in accordance with Islamic teachings. In this context, perfection refers to the achievement of educational goals through continuous development of physical and spiritual potential, or the dimensions of al-jismiyah (physical) and ruhiyah (spiritual). The urgency of studying educational psychology in Islam, based on the Qur'an, lies in its role as a method and medium for refining one's soul, which is reflected in personality and behavior in daily life. The goal is to find solutions to transform students' behavior towards betterment and to achieve an ideal Islamic personality (mutmainnah).